Penerapan Sistem Manajemen Lingkungan (ISO 14001.2004) Pada Proses Konstruksi Gedung Kantor Dinas Pekerjaan Umum (PU) Provinsi Riau - Khairul Rizal; Aras Mulyadi; Manyuk Fauzi (Universitas Riau, 2016)
Construction of the new office building for Public Work Department based on condition of the old building on Riau Street no. 1 Pekanbaru that cannot accommodate official activities, narrow area include with the cause of the traffic jamming in the intersection at Jenderal AhmadYani street.The Government of Riau Province through Public Work Department plans a new modern building office, and becomes the first building in Sumatra that applies green building concept. The aim of the research is to describes perseption from all who mixed up in the project to the application of ISO 14001.2004 and to analizes the application performance during the construction. The primary data is taken by range survey in the project site, the sample is taken by purposive sampling from the owner, consultant, and contractor population. From the research known that 48% respondents clarify the data is formally appropriate and perfectly fullfill the criteria in determine the principals of ISO 14001, while 46% clarify that some of those principals needs to be enhanced and 6% respondents clarify that there is unappropriation in the application. In the process of the building construction, PT. Waskita Karya (Persero) as the contractor has no satisfaction performance inenviromental management system yet, considering that PT. Waskita Karya (Persero) has low performance in some of the principals of ISO 14001.2004.